2015
DOI: 10.1002/gcc.22264
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT signaling inhibits NOTCH1 lysosome‐mediated degradation

Abstract: The pathways of NOTCH and PI3K/AKT are dysregulated in about 60% and 48% of T-cell acute lymphoblastic leukemia (T-ALL) patients, respectively. In this context, they interact and cooperate in controlling tumor cell biology. Here, we propose a novel mechanism by which the PI3K/AKT pathway regulates NOTCH1 in T-ALL, starting from the evidence that the inhibition of PI3K/AKT signaling induced by treatment with LY294002 or transient transfection with a dominant negative AKT mutant downregulates NOTCH1 protein leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The above evidence that the IL-4-induced increase in Notch1/2 activation was independent of Jag1 upregulation prompted us to investigate the molecular pathways responsible for this event. It has been shown that in T-ALL cells, a role in promoting deregulated Notch1 activation is played by an excessive PI3K/AKT signaling 53 . Based on these observations and given the hyperactivation of PI3Kδ/AKT signaling in CLL 38 , 49 and our evidence that IL-4 further increased PI3Kδ/AKT activity, we examined whether inhibiting this pathway could contrast the stimulatory effect of IL-4 on Notch1 expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above evidence that the IL-4-induced increase in Notch1/2 activation was independent of Jag1 upregulation prompted us to investigate the molecular pathways responsible for this event. It has been shown that in T-ALL cells, a role in promoting deregulated Notch1 activation is played by an excessive PI3K/AKT signaling 53 . Based on these observations and given the hyperactivation of PI3Kδ/AKT signaling in CLL 38 , 49 and our evidence that IL-4 further increased PI3Kδ/AKT activity, we examined whether inhibiting this pathway could contrast the stimulatory effect of IL-4 on Notch1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these events regulating Notch activation are in turn regulated by signaling pathways often aberrantly activated in tumor cells. In T-ALL cells, hyperactive PI3K/AKT signaling deregulates Notch1 activation inhibiting its lysosome-mediated degradation 53 . In breast cancer stem cells, high levels of prolyl-isomerase Pin1 sustain Notch signaling protecting Notch1 and Notch4 from proteasomal degradation 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Total cells protein were extracted with RIPA lysis buffer as previously reported [ 69 ]. Protein samples (40 μg) were run on a 4-12% NuPAGE gel (ThermoScientific), transferred onto a nitrocellulose membrane (Biorad), and blocked with 5% non-fat milk in TBS-T (20 mM Tris-Cl, pH 7.5, 150 mM NaCl, 0.05% Tween-20).…”
Section: Methodsmentioning
confidence: 99%
“…Besides this canonical Notch pathway, in oncogenesis and inflammation, it has been described a non-canonical Notch signaling which is γ-secretase independent ( 3 ). Notch signaling is tightly controlled by several mechanisms, including degradation mediated by the proteasome and lysosome machineries ( 4 , 5 ). The cancer-related aberrant activation of Notch pathway affects the biology of the single tumor cell and its interaction with the surrounding microenvironment ( 6 ).…”
Section: Introductionmentioning
confidence: 99%